The effects of student organization participation on Chinese university students’ non-cognitive skills: An empirical analysis based on CFPS data - Ye, Zichen; Hu, Fengxia; Yu, Miao (Edelweiss Applied Science and Technology, 2026)
Non-cognitive skills have become increasingly important in the digital era. Given the role of student organizations in facilitating social interaction and informal learning, they may contribute to the development of these skills among university students. However, empirical evidence remains limited. On this basis, the study uses data from the China Family Panel Studies (2018–2022) conducted by the Institute of Social Science Survey at Peking University. By constructing a baseline regression model, it systematically analyses the promotional effects of student organization participation on students' non-cognitive skills and potential heterogeneity issues. Results indicate that student organization participation significantly improves non-cognitive skills, and the findings remain robust across alternative specifications. After applying Propensity Score Matching to mitigate endogeneity, the promotional effect markedly increases, exhibiting heterogeneity across different household registration statuses and per capita family incomes. This study extends the research on the formation mechanisms of non-cognitive skills and deepens academic understanding of the educational functions of student organizations. The findings provide valuable implications for higher education institutions seeking to optimize talent cultivation strategies and improve the development of student organizations, while the heterogeneity analysis offers new insights into promoting educational equity.